(untitled) (Fiep Bulletin - online, 2013)
This study aims to verify the process in dance history looks back to its current status. The literature review identified that performed the dance in this whole process of civilization along the society and serving as a means to express the man. Thus the dance this throughout this process of civilization and accompanying social developments, see themselves with the teachers of Physical Education that the school has the content, with the academies of high income, highly accessible with the media. Finally, there is still movement and expression of feelings if historical understanding of art more complete and the old world.